Persisting hyperekplexia after idiopathic, self-limiting brainstem encephalopathy. - van de Warrenburg, B; Cordivari, C; Brown, P; Bhatia, K (2007)
Symptomatic hyperekplexia is a relatively rare entity, but has been documented in various, mostly brainstem diseases. We report the clinical and neurophysiologic vignette of a patient with a self-limiting, possibly inflammatory brainstem encephalopathy. Trismus was the presenting feature, but she later developed hyperekplexia. Although most brainstem features resolved spontaneously, the hyperekplexia has persisted.